Adult-Onset Type 1 Diabetes and Pregnancy: Three Case Reports. (28th March 2013) - Bonsembiante, Barbara; Dalfrà, Maria Grazia; Masin, Michela; Gallo, Alessandra; Lapolla, Annunziata
Abstract : From 5% to 10% of diabetic patients have type 1 diabetes. Here we describe three cases of adult-onset type 1 diabetes in pregnancy treated at our clinic between 2009 and 2012. Two patients came for specialist examination during pregnancy, the third after pregnancy. These women had no prior overt diabetes and shared certain characteristics, that is, no family diabetes history, age over 35, normal prepregnancy BMI, need for insulin therapy as of the early weeks of pregnancy, and high-titer anti-GAD antibody positivity. The patients had persistent diabetes after delivery, suggesting that they developed adult-onset type 1 diabetes during pregnancy. About 10% of GDM patients become pancreatic autoantibody positive and the risk of developing overt diabetes is higher when two or more autoantibodies are present (particularly GAD and ICA). GAD-Ab shows the highest sensitivity for type 1 diabetes prediction. We need to bear in mind that older patients might conceivably develop an adult-onset type 1 diabetes during or after pregnancy. So we suggest that women with GDM showing the described clinical features shall be preferably tested for autoimmunity. Pregnant patients at risk of type 1 diabetes should be identified to avoid the maternal and fetal complications and the acute onset of diabetes afterwards.